Change in Quality of Life for Patients with Irritable Bowel Syndrome following Referral to a Gastroenterologist: A Cohort Study. - Caroline Canavan; Joe West; Timothy Card (PLoS ONE)
Background Irritable bowel syndrome (IBS), a chronic functional condition, considerably reduces quality of life (QoL) and referral to gastroenterology is common. Until now, however, the impact of seeing a gastroenterologist for IBS on patients' QoL and utility has not been assessed. Methods Patients referred with "probable IBS" to the Nottingham Treatment Centre between October 2012 and March 2014 were invited to complete a QoL questionnaire (EuroQol-5 Dimension) before their first appointment. Patients with confirmed IBS who completed this baseline assessment were sent follow-up questionnaires three and twelve months later. Global QoL and utility were measured at each time point and change from baseline calculated. Paired t-tests analysed the significance of any change. Results Of 205 invited patients, 69 were eligible and recruited. Response at three and twelve months was 45% and 17% respectively. Median global QoL at baseline was 67.5 (Interquartile range [IQR] 50.0 to 80.0), with a mean increase of 3.25 (95% confidence interval [CI] -5.38 to 11.88) three months later and a mean decrease of -1.82 (95% CI -16.01 to 12.38) after one year. The median utility at baseline was 0.76 (IQR 0.69 to 0.80), with a mean increase of 0.06 (95%CI -0.01 to 0.14) at three months and no change, 0.00 (-0.16 to 0.16), after one year. Conclusion Patients experienced a small but not statistically significant increase in QoL and utility three months after seeing a gastroenterologist for IBS, which was not maintained. Gastroenterology referral does not appear to appreciably improve Qol for most people with IBS.